Error performance of multi-branch dual-hop PF cooperative systems - Guangqiu LI; Jiayun DONG; Tao JIANG (Dianxin kexue)
Design of multi-branch dual-hop phase-only forward(PF)cooperative systems with continuous phase frequency shift keying(CPFSK)modulation needs to determine the number of branch and modulation index.The usual solution of determining the above parameters is the time-consuming and inefficient computer simulation.An efficient solution of determining these parameters is theoretical analysis method.Semi-analytical expressions for the average bit error rate(ABER)of multi-branch dual-hop PF cooperative systems in conjunction with discrimination detection CPFSK over time-selective Rayleigh fading channels was presented.Two cases with and without antenna selection at the relays and maximum-ratio combining(MRC)receive diversity at the destination were considered.The simulation results show that numerical calculation results and simulation results for the ABERs of PF，discrimination detection,CPFSK cooperative systems are consistent and show that the above ABER theory results of CPFSK cooperative systems can be used to design PF cooperative systems.